Gender and Competition: Evidence from Academic Promotions in France - Clément Bosquet; Pierre-Philippe Combes; Cecilia Garcia-Pe\~nalosa (Center for Economic Studies and ifo Institute (CESifo), 2013)
Differences in promotion across genders are still prevalent in many occupations. Recent work based on experimental evidence indicates that women participate less in or exert lower effort during contests. We exploit the unique features of the promotion system for French academics to look at women's attitudes towards competition in an actual labour market. Using data for academic economists over the period 1991-2008 we find that, conditional on entering the competition, there is no difference in promotions across the genders, which is difficult to reconcile with either discrimination or a poorer performance of women in contests. In contrast, women have a substantially lower probability than men to enter the promotion contest. Our data does not support that this gap is due to differences in costs or preferences concerning department prestige, indicating that women are less willing than men to take part in contests.
Keywords: J16; J70; I23; 330; gender gaps; promotions; academic labour market